1996
DOI: 10.1056/nejm199602013340504
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Continuous Intravenous Epoprostenol (Prostacyclin) with Conventional Therapy for Primary Pulmonary Hypertension

Abstract: As compared with conventional therapy, the continuous intravenous infusion of epoprostenol produced symptomatic and hemodynamic improvement, as well as improved survival in patients with severe primary pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
1,522
5
62

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,457 publications
(1,649 citation statements)
references
References 29 publications
39
1,522
5
62
Order By: Relevance
“…Second prospective randomised open trial reported improvement in 6MWT by 32 m, in the epoprostenol group after 12 weeks of therapy. 40 Survival advantage was also demonstrated in this trial in the group of patients on epoprostenol. Following these studies, intravenous epoprostenol was approved in USA and France for treatment of iPAH for those in functional class III or IV.…”
Section: Epoprostenolsupporting
confidence: 59%
See 2 more Smart Citations
“…Second prospective randomised open trial reported improvement in 6MWT by 32 m, in the epoprostenol group after 12 weeks of therapy. 40 Survival advantage was also demonstrated in this trial in the group of patients on epoprostenol. Following these studies, intravenous epoprostenol was approved in USA and France for treatment of iPAH for those in functional class III or IV.…”
Section: Epoprostenolsupporting
confidence: 59%
“…To date it is the only medication that has a mortality benefit. 40 Intravenous epoprostenol is now considered as a first line therapy in the western world. In a survey collected from 19 centres in the US, it was shown that more than two-thirds of patients with iPAH who were treated with intravenous epoprostenol could be taken off the list for lung transplantation.…”
Section: Epoprostenolmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] However, epoprostenol has several inherent drawbacks. Epoprostenol is administered through continuous intravenous infusion, and its dosing and regulation is complex.…”
Section: Introductionmentioning
confidence: 99%
“…Prostacyclin has vasodilatory, anti-proliferative, anti-inflammatory and antithrombotic properties and is therefore an important target substance in PAH-specific therapy [1] . Epoprostenol was the first specific therapy approved for the treatment of PAH, after showing a positive effect on survival [2] . Epoprostenol is chemically unstable with a short biological half-life of 3-5 min, and must be continuously administered by intravenous (IV) infusion using an external pump and indwelling central venous catheter.…”
Section: Introductionmentioning
confidence: 99%